PENERAPAN SISTEM INFORMASI UNTUK MANAJEMEN DATA MINERAL - Prayogo, Teguh (Jurnal Sains dan Teknologi Indonesia, 2009)
Mineral Information System (SIM) is an added value and integrated database system for mineral in Indonesia concerning with the availability of mineral resources, which encompasses the entire aspects of mineral commodity such as geology, mining, geography, exploration, exploitation, processing technology,statistics and its developments. The technologies used in the SIM development are appropriate technology, open platform, Visual Programming using Rapid Application Development tools, and Relational Database Management System (RDBMS). The SIM technology enables users to illustrate and display someinformations regarding to mineral resources easily and rapidly, i.e. local governments, investors, or persons who are interested in mining or mineral development. The SIM technology is benefit for decision makers to support a regulation or urban planning. In this paper, it will be described about visualization model of SIM in application desktop form.